The significance of preclinical anti-BP180 autoantibodies - Mai, Yosuke; Izumi, Kentaro; Mai, Shoko; Ujiie, Hideyuki (Frontiers in Immunology, 2022)
Bullous pemphigoid (BP) is the most common autoimmune subepidermal blistering disease. Although the pathomechanism of BP onset has yet to be elucidated in detail, BP autoantibodies targeting two hemidesmosomal components, BP180 and BP230, are known to play a pivotal role in BP pathogenesis. Thus, the detection and measurement of BP autoantibodies are necessary for diagnosing BP and monitoring the disease activity. Immune assays such as immunofluorescence microscopy, immunoblotting, and ELISAs using BP180 and BP230 detect BP autoantibodies in most BP cases with high specificity; however, BP autoantibodies are sometimes detected in BP patients before the onset of this disease. BP autoantibodies that are detected in patients without typical tense blisters are defined as “preclinical BP autoantibodies”. These preclinical BP autoantibodies are detected even in a low percentage of normal healthy individuals. Although the importance of preclinical BP autoantibodies remains elusive, these autoantibodies might be a potential risk factor for subsequent BP development. Therefore, previous comparative epidemiological studies have focused on the prevalence of preclinical BP autoantibodies in populations susceptible to BP (e.g., the elderly) or in diseases with a higher risk of comorbid BP. This mini-review summarizes the literature on the prevalence of preclinical BP autoantibodies in patients with various conditions and diseases, and we discuss the significance of preclinical BP autoantibody detection.